"Inexpressible horror": The Devil and Baptist Life Writing in Cromwellian Ireland. Issue 3 (September 2020) - Gribben, Crawford
Abstract: The Baptist movement in Cromwellian Ireland displayed a number of distinctive features. Adherents of the movement regularly claimed to have heightened spiritual experiences, which in a number of cases included firsthand encounters with the devil. This article observes the political contexts in which these claims were made while analyzing attempts by Baptist leaders to promote a more critical spirituality and counter illegitimate claims to supernatural experience. It argues that these unusual experiences, reflective more of their geographical than their denominational context, were rhetorically enabled, and Baptist leaders would struggle to both sustain and contain claims to spiritual experience.